Pendampingan Pembuatan Media Pembelajaran Virtual bagi Guru IPA SMP se-Kabupaten Semarang - Khoiri, Nur; Ristanto, Sigit; Huda, Choirul; Saefan, Joko; Kurniawan, Wawan (Journal of Dedicators Community, 2022)
One of the reasons for the lack of student learning motivation is the unavailability of learning media that can focus students' attention and help students understand science concepts. The purpose of this PKM activity is to provide assistance to science teachers in overcoming difficulties in the absence of learning media as a tool in the science learning process in junior high schools. The specific target of this PKM is to design, create and use virtual learning media for physics/science materials. The output of this activity is a physics/IPA learning media package for junior high schools. The method used in this activity is mentoring and training. Activities in this PKM are mentoring and training in designing, creating and using virtual learning media for junior high school physics/science materials. This activity was carried out for 32 hours of lessons and monitoring the use of learning media by MGMP physics/IPA teachers in Semarang Regency for 3 months. Activities that have been carried out to overcome partner problems are designing virtual learning media using several Power Point Presentation Developer software, Video Tracker, Latex and PheT. The series of activities consists of four main stages, namely media design, media creation, media use and testing of virtual learning media for junior high school physics/science materials. Junior high school physics/science teachers succeeded in making learning media using Power Point Presentation Developer and Phet on the concepts of temperature and heat